Strategi Pemasaran Jasa Pendidikan dalam Meningkatkan Animo Masyarakat pada Masa Pandemi Covid-19 - Mahmud MY; Riftiyanti Savitri; Lesiana Oktorita (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2021)
This research aims to find out the management of marketing of educational services in increasing public interest during the Covid-19 pandemic. This research uses descriptive qualitative research methods. Data is collected through observations, interviews, and documentation. The results of the study showed that the marketing of ma Al-Azhar Muaro Bungo education services during the Covid-19 pandemic was carried out by applying the concept of educational services marketing mix including marketing quality graduate products and karimah; price (tuition fee) is determined by the adjustment of the average economy of the student's parents; the place or location of the madrassa is in a strategic location; madrassa promotion is carried out directly and indirectly; Professional human resources and adequate facilities and infrastructure; The process of delivering educational services includes the delivery of facilities and facilities, learning activities, and extracurricular activities.